PENINGKATAN SELF CARE SEBAGAI UPAYA PASIEN PASCA STROKE - Nurul Hidayah; Rahmi Syarifatun Abidah (HOSPITAL MAJAPAHIT : JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO, 2024)
The impacts caused by stroke include weakness or paralysis of the extremities and impaired vision due to limited field of vision. This causes the inability of stroke sufferers to carry out activities and self-care independently. This study aims to determine the efforts of post-stroke patients in improving self-care in Ngampelsari Village, Candi District, Sidoarjo Regency. The design of this study is a descriptive case study consisting of 2 subjects as respondents according to the specified criteria. This study was conducted on June 11, 2024 - June 15, 2024. Data collection was carried out by interviews and observations. Sample selection was carried out in pairs (matching). The results of the study showed that the subjects had made efforts to improve self-care needs which included meeting the needs for air, drinking, eating, elimination and cleanliness, activities and rest, solitude and social interaction, prevention from danger, and increasing development in social groups